OS DESAFIOS PARA A IDENTIFICAÇÃO DO PSICOPATA NO SISTEMA PRISIONAL BRASILEIRO - CÂNDIDO, ROBERLÂNIO MOURA (2023)
In the Brazilian penal system, the accurate identification of psychopaths has been a complex and challenging issue. Although the legal definition of imputability is clearly established in the Penal Code, psychopaths do not fall into this category, since, even due to personality disorders, they are aware of the illegality of their criminal acts, being mostly considered as semi-imputable by our order. The search for understanding what psychopathic behaviour could be goes back to antiquity, with its most relevant innovation brought by Cleckley with the 16 characteristics that would contribute to the identification of the psychopath in addition to a new perspective in this sense. Furthermore, the current instruments for this diagnosis are quantitative and qualitative, such as the PCL-R and the Rorschach Test. However, it is essential that when analysing the agent's conduct considered illegal, it is also necessary to evaluate his volitional and intellective capacity, using our order, when dealing with this analysis, the Biopsychological criterion. The structural flaws presented by the Brazilian penal system often end up being exploited by psychopaths for their own benefit, damaging the environments in which they are inserted. As a result, there are questions regarding the effectiveness of this diagnosis as well as the assessment of the cessation of dangerousness. Still under the aegis of compliance with the psychopath's sanction, the prison environment ends up having no effect, at least in its current form, in relation to these individuals. This point raises a crucial question: are the procedures and tests used in the Brazilian penal system really efficient in identifying psychopathy? According to the WHO, psychopathy is considered a personality disorder, not a mental illness, and can be classified in varying degrees, from mild to severe. Psychopaths have a peculiar and characteristic way of being, which, regardless of the degree, makes social interaction challenging. It is important to highlight that not all psychopaths are murderers, as they are often portrayed in the media. However, the precise diagnosis of psychopathy has been problematic, mainly due to the manipulative and persuasive behaviour of psychopaths themselves, who often manage to convey a "satisfactory" image to evaluators, due to the limitations encountered whether in the professional field or in relation to the limitation of available financial resources, which directly reflect on the evaluation techniques currently administered in the Brazilian penal system. This inaccuracy in diagnosis can have serious consequences, not only in isolation, but also more broadly, by not adequately identifying psychopaths and potentially posing risks to the community in which they are located. It is essential to highlight that accurate identification has significant implications in the determination and correct application of sentences, as well as in risk management and public security as a whole, also considering the constitutional principle of individualization of the sentence in accordance with Art. 5th item XLVI of the Brazilian Constitution. Therefore, this TCC aims to understand the needs for a more effective sentence, analysing procedures used by professionals in the Brazilian penal system to identify psychopathy and its legal and social implications. Furthermore, it seeks to understand the doctrine on imputability, evaluate the diagnostic processes of psychopathy in the criminal context and its impact on the environments in which they are inserted. In this context, it is crucial to improve procedures for identifying psychopathy in the Brazilian prison system, seeking to develop more accurate and updated techniques that consider the complexity of this personality disorder. The methodology involved both qualitative and quantitative research, through bibliographic analyses in books, articles and other final papers, as well as authorial interviews carried out between the months of September and October 2023 at the Hospital de Custódia Psiquiátrico Jorge Vaz- MG, at the Santa Luzia Prison - MG and at the Forensic Psychiatry Hospital – JP. After intense analysis, it was found that in fact there is no identification of psychopaths in our penal system, at least not as it should be, and furthermore, there is, therefore, no separation, much less a specific place to keep them separate from others that make up the prison population. In addition to this, several other problems were identified within the penal system, reinforcing the imperative need for a specific norm under this umbrella in order to seek to fill this gap in our legal system. Adequate understanding of psychopathy and its accurate identification are fundamental to the treatment and rehabilitation of affected individuals, as well as to promoting a safer society.